The arts of citizenship in African cities : infrastructures and spaces of belonging - Diouf, Mamadou; Fredericks, Rosalind (2014)
"Building upon a growing literature that resists the pathologizing effects of developmentalist and comparative framings, this fascinating collection of case studies pushes the frontiers of scholarship on African urbanism through detailed and nuanced ethnographic analyses of life in a diverse set of cities across the continent. These contributions explore a range of innovative institutions, discourses, and material practices through which claims to citizenship are enacted and contested by a diverse array of actors. They treat cities as sites of experimentation, privileging the ordinary, daily, under-the-radar negotiations through which emergent reconfigurations of citizenship are being continually forged. In doing so, they provide a more culturally informed perspective on African politics and society"--
Introduction / Rosalind Fredericks and Mamadou Diouf -- 1. Too Many Things to Do : Social Dimensions of City Making in Africa / AbdouMaliq Simone -- 2. The Funeral in the Village : An Ultimate Test for African Urbanites? : Shifting Imaginations of Belonging, Mobility and Community / Peter Geschiere -- 3. Citizenship and Civility in Peri-Urban Mozambique / Juan Obarrio -- 4. "Dealing with the Prince over Lagos" : Pentecostal Arts of Citizenship / Ruth Marshall -- 5. The Road to Redemption : Performing Pentecostal Citizenship in Lagos / Adedamola Osinulu -- 6. "The Old Man is Dead" : Hip Hop and the Arts of Citizenship of Senegalese Youth / Rosalind Fredericks -- 7. Beautifying Brazzaville : Arts of Citizenship in the Congo / Remy Bazenguissa-Ganga -- 8. Representing an African City and Urban Elite : The Nightclubs, Dance Halls, and Red Light District of Interwar Accra / Jinny Prais -- 9. Seeing Dirt in Dar es Salaam : Sanitation, Waste and Citizenship in the Post-Colonial City / Emily Brownell -- 10. "Ambivalent Cosmopolitans"? : Senegalese and Malian Migrants in Johannesburg / Christine Ludl -- 11. Walls and White Elephants : Oil, Infrastructure, and the Materiality of Citizenship in Urban Equatorial Guinea / Hannah Appel -- 12. Nigerian Modernity and the City : Lagos, 1960 - 1980 / Giles Omezi.
Includes bibliographical references.
Keywords: Cities and towns -- Africa -- History; City and town life -- Africa -- History; Urbanization -- Africa -- History; Citizenship -- Africa -- History; Public spaces -- Africa -- History; Politics and culture -- Africa -- History; Sociology, Urban -- Africa; SOCIAL SCIENCE / Anthropology / General; SOCIAL SCIENCE / Sociology / Urban; SOCIAL SCIENCE / Developing Countries; Africa -- Social life and customs; Africa -- Social conditions; Africa -- Politics and government